Edukasi Kesehatan Ibu dan Anak sebagai Investasi Masa Depan Bangsa di Desa Damping, Kabupaten Serang - Qonita, Qonita; Zahrah, Nisri Ina; Rismawati, Rismawati; Fauziah, Cici Nurul; Junaedi, M. Faturohman; Wirawan, Andini; Amaliyah, Nina (IMPACT: Journal of Community Service, 2025)
Maternal and Child Health (MCH) is one of the key indicators of public health development and a priority in achieving the Sustainable Development Goals (SDGs). Pregnant women and children are among the most vulnerable groups to health problems due to their high risk of pregnancy complications, infectious diseases, malnutrition, and growth and developmental disorders. Based on this condition, a community service program was conducted to improve the knowledge of residents in Damping Village, Pamarayan Subdistrict, Serang Regency, regarding maternal and child health. The implementation method consisted of problem identification, priority analysis, planning, health education using leaflets, and evaluation through pre-test and post-test assessments. The activity was attended by 30 participants, consisting of health cadres and couples of reproductive age. The results showed a significant increase in knowledge: the percentage of participants with poor knowledge decreased from 70% before the session to 20% after, while those with good knowledge increased from 30% to 80%. These findings indicate that interactive counseling using attractive leaflets is effective in enhancing community understanding of maternal and child health.